Recombinant ATPase of Virulent Aeromonas hydrophila Protects Channel Catfish Against Motile Aeromonas Septicemia - Abdelhamed, Hossam; Banes, Michelle; Karsi, Attila; Lawrence, Mark L. (Frontiers in Immunology, 2019)
Channel catfish farming dominates the aquaculture industry in the United States. However, epidemic outbreaks of motile Aeromonas septicemia (MAS), caused by virulent Aeromonas hydrophila (vAh), have become a prominent problem in the catfish industry. Although vaccination is an effective preventive method, there is no vaccine available against MAS. Recombinant proteins could induce protective immunity. Thus, in this work, vAh ATPase protein was expressed, and its protective capability was evaluated in catfish. The purified recombinant ATPase protein was injected into catfish, followed by experimental infection with A. hydrophila strain ML09-119 after 21 days. Results showed catfish immunized with ATPase exhibited 89.16% relative percent survival after challenge with A. hydrophila strain ML09-119. Bacterial concentrations in liver, spleen, and anterior kidney were significantly lower in vaccinated fish compared with the non-vaccinated sham group at 48 h post-infection (p < 0.05). Catfish immunized with ATPase showed a significant (p < 0.05) higher antibody response compared to the non-vaccinated groups. Overall, ATPase recombinant protein has demonstrated potential to stimulate protective immunity in catfish against virulent A. hydrophila infection.